Comparing the outcomes of incisions made by colorado microdissection needle, electrosurgery tip, and surgical blade during periodontal surgery: A randomized controlled trial - Rampalli Viswa Chandra; Boya Savitharani; Aileni Amarender Reddy (Wolters Kluwer Medknow Publications, 2016)
Context: Electrosurgery offers many unique advantages such as hemostasis and precise tissue cutting; however, there are a number of disadvantages including thermal injury and delayed wound healing. Aims: The aim of the present study was to compare the outcomes of incisions made by Colorado® microdissection needle, electrosurgery tip, and surgical blade during periodontal surgery. Settings and Design: Twenty-two individuals participated in this study. Three quadrants in each individual were randomly assigned into each of the following experimental groups: Colorado® microdissection needle (CMD), electrosurgery tip (EC) and surgical blade (BP), in which, incisions were given with Colorado® microdissection needle, straight electrocautery tip, and a scalpel blade, respectively. Materials and Methods: Blood loss (BL) was measured immediately after surgery, and changes in interdental papilla dimensions were recorded at baseline, 7, 30, 120, and 180 days after surgery. Measures of periodontal disease were recorded at baseline, 120, and 180 days after surgery. Postoperative pain and wound healing were recorded at 1, 7, and 15 days after surgery. Results: The use of CMD for periodontal surgery showed better results over EC in all parameters. CMD resulted in lesser bleeding and less postoperative pain and attained similar results to that of BP in clinical parameters of periodontal disease. Conclusions: Colorado® microdissection needle may be a better choice for incisions as it seems to show less tissue damage than cautery and offers tissue healing comparable to scalpel blade.